2006
DOI: 10.1063/1.2168687
|View full text |Cite
|
Sign up to set email alerts
|

Nonbolometric photoresponse in (La,Pr)0.67Ca0.33MnO3 thin films

Abstract: We have studied light-induced resistance changes (photoresponse) in the colossal magnetoresistive manganite material (La,Pr)0.67Ca0.33MnO3. The metal-insulator transition in this material is understood to be driven by the percolation of the metallic channel in an inhomogeneous matrix of insulating and metallic components. Our experiments reveal a nonthermal (nonbolometric) component of the light-induced resistance change, in addition to the expected resistance change related to heating (bolometric effect). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…As the temperature coefficient (dR/dT) below T MI /T IM is positive, the heating effect caused by laser will increase the resistance and the resistance will drop after the light is switched off. 15,21 The observed PPC effect is independent of the polarity and magnitude of bias current [see Fig. 4(b)].…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…As the temperature coefficient (dR/dT) below T MI /T IM is positive, the heating effect caused by laser will increase the resistance and the resistance will drop after the light is switched off. 15,21 The observed PPC effect is independent of the polarity and magnitude of bias current [see Fig. 4(b)].…”
Section: -mentioning
confidence: 99%
“…The studies on photo-induced effects are quite active but not as extensive as those on CMR effects. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The origin of these effects has not been well-understood yet. Miyano et al demonstrated a photo-induced transition from chargeordered state to metallic state in an electric-field biased Pr 0.7 Ca 0.3 MnO 3 single crystal.…”
mentioning
confidence: 99%